Comparison of gene transfer into the cochlea using adeno-associated virus versus adenovirus vectors - Yang, Yang; Kong, Wei-jia; Hu, Yu-juan; Zhong, Yi; Zhao, Xue-yan; Peng, Wei (Zhong hua yi xue za zhi, 2009)
To determine which of the two, recombinant adeno-associated viral vector 2 (rAAV2) and recombinant adenovirus vector 5 (rAd5), is more suitable for gene transfer in rodent cochlea. The rAAV2-EGFP and rAd5-EGFP particles were injected into the perilymph through round window membrane. The target tissue accessibility, time course of expression, tissue toxicity of gene transfer and effects on hearing were evaluated. The expression of EGFP was detected in spiral ligament, strial vascukarises, Reissner membrane, basilar membrane, spiral ganglion, and contralateral cochlea. EGFP expression in the rAAV2 lasted over 60 days, with peak expression between days 14 and 60. EGFP in the rAd5 was detected within 24 h of transfection, and peak expression was observed between days 1 to 21. EGFP activity decreased sharply on day 30 after transfection with rAd5, while high EGFP expression was observed 60 days after transfection with rAAV2. AAV has significant advantages for long-term transgene expression and no ototoxicity in th